Cobalt tris(4-vinylphenyl)corrole: out of the frying pan into the polymer. Issue 15 (31st January 2023) - Desbois, Nicolas; Osterloh, W. Ryan; Sabat, Dimitri; Monot, Camille; Brandès, Stéphane; Meyer, Michel; Chaar, Capucine; Hespel, Louise; Lebrun, Laurent; Baati, Rachid; Estour, François; Gros, Claude P.
Abstract : A novel cobalt corrole bearing 4-vinylphenyl groups at the 5, 10, 15- meso -positions of the macrocycle has been synthesized from tris(4-bromophenyl)corrole using a Suzuki coupling reaction. Abstract : A novel cobalt corrole bearing 4-vinylphenyl groups at the 5, 10, 15- meso -positions of the macrocycle has been synthesized from tris(4-bromophenyl)corrole using a Suzuki coupling reaction. The spectral and electrochemical properties are reported in CH2 Cl2 along with its ability to form a highly stable six-coordinate complex and cross-linked corrole-based polymer in a 59% yield.